Solution
The general form of an exponential function is
![y=a(b)^x+c](https://img.qammunity.org/2023/formulas/mathematics/college/ztywpxl7w5t4c5vmrjxtpmf4of0xftrck5.png)
The graph of the function is inverted and shifted by 7 units to give
![y=-a(b)^x+7](https://img.qammunity.org/2023/formulas/mathematics/college/b37ta8ctawrg22w3o7gcqjrpc3lsxepnga.png)
Where
![x=0,y=5](https://img.qammunity.org/2023/formulas/mathematics/college/o1rc7s0oibvoewogyclmhuptoeg17ho0kr.png)
Substitute for x and y in the general form of an exponential function
![\begin{gathered} y=-a(b)^x+7 \\ 5=-a(b)^0+7 \\ 5=-a(1)+7 \\ 5=-a+7 \\ \text{Collect like terms} \\ a=7-5 \\ a=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6lgx3l16rz4op44021t11rdbewe9rmolyp.png)
Where x = 1, y = 0.5, substitute into the function
![\begin{gathered} y=-a(b)^x+7 \\ 0.5=-2(b)^1+7 \\ 0.5=-2b+7 \\ \text{Collect like terms} \\ 2b=7-0.5 \\ 2b=6.5 \\ \text{Divide both sides by 2} \\ (2b)/(2)=(6.5)/(2) \\ b=(13)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i673o0xgjg6c6zhxxbyt8wpxj17u0awywe.png)
The exponential function is
![y=-2((13)/(4))^x+7](https://img.qammunity.org/2023/formulas/mathematics/college/23sngs1vydvpma61bctc23gex04w6c0lau.png)
Hence,
The coefficient, a, is -2.
The base is, b, 13/4
The exponent is x
The constant, c, we adding to our function is 7